## Trending News

# Given: F(2)=3, F'(2)=4, F(3)=8, F'(3)=7 Find: [F^-1(8)]'?

I'm in AP Calculus

There is no f(x)

### 10 Answers

- Anonymous1 decade agoFavorite Answer
Are you SURE F'(3) = 7????

- lifordLv 44 years ago
in simple terms some issues Dave S.... - The F22 is an surprising airplane little doubt. yet i've got spoken to 3 typhoon pilots, and that they are asserting that they are able to nevertheless "see" the F-22's warmth signature BVR utilising the IR sensor on the nostril. All information from the radar, and any warmth signatures are all displayed utilising sensor fusion on the map. Even aims from different Typhoons interior the section would be exhibited to the pilot. - A Eurofighter typhoon coach "Shot Down" 2 F15's (2 on a million) for the time of a flight over the Lake District. - The typhoon has supercruise features besides (around Mach a million.5) and the F-22 is reportedly around Mach a million.7 . to respond to your question: Its shown that the typhoon can "shoot down" an F-15. no be counted if it may "shoot down" an F22 is yet another question. The pilots that i've got spoken to nevertheless shelter that its conceivable simply by fact the F22's radar stealth would not catch up on the aircrafts warmth signature (which could be picked up by utilising typhoon previous seen variety). the only thank you to confirm may well be to have a dogfight :-) .

- PuggyLv 71 decade ago
Presuming F is one-to one, if F(3) = 8, then we take the functional inverse of both sides to obtain

F^(-1)(F(3)) = F^(-1)(8)

3 = F^(-1)(8)

I have absolutely no clue what role the derivatives played. But at first glance, this is my answer.

EDIT: I missed the apostrophe at the end. I'm not sure how to do the rest of the question.

- Jason LLv 51 decade ago
1. F^-1(x) is not 1/F(x) It is reverse function or it will use the notation 1/F(X).

2. Use Chain Rule twice.

Use Chain Rule:

u=g(x)

y=f(u)

So y = f(g(x))

Then dy/dx = dy/du * du/dx

[f(g(x)]' = f'(g(x)) * g'(x)

g'(x) = [f(g(x))]' / f'(g(x))

Let's make G(x) be F^-1(x) and we got:

[G(x)]' = [F(G(x))]' / [F(x)]'

-> [F^-1(x)]' = [F(F^-1(x)]'/[F(x)]'

-> [F^-1(8)]' = [F(F^-1(8))]'/[F(8)]'

-> [F^-1(8)]' = [F(3)]'/[F(8)]'

-> [F^-1(8)]' = 7/[F(8)]'

Let's find F'(8)

Let u=G(x) = x^3

y = F(u)

F'(G(x)) = G'(x) * F'(x)

F'(G(x)) = 3 * x^2 * F'(x)

Let x = 2

Then F'(8) = 3 * 2^2 * F'(2) = 3 * 4 * 4 = 48

So [F^-1(8)] = 7/[F(8)]' = 7 / 48

- How do you think about the answers? You can sign in to vote the answer.
- 1 decade ago
[F^-1(8)]' = - F'(8)/F(8)

F(x) = ax^3+bx^2+cx+d

F'(x)= 3ax^2+2bx+c

solving F(x) we get a=1 b=-6 c=16 d=-15

F(x) = x^3-6x^2+16x-15

F(8) =241

F'(8)=48

the answer is - 48/241

- Anonymous1 decade ago
F^-1(8) = 3

This is a number, so, its derivative is 0.

Edited:

The following answer sounds right to me. Harry's hypothesis is interesting, but noone knows if f is a 3rd grad polynomials.

Ana

- 1 decade ago
Ummm, I'm in AP Calculus also, but... gotta tell you, I have no idea... I don't know if we've learned that yet...

- sahsjingLv 71 decade ago
[F^-1(8)]' = 1/F'(3) = 1/7

If you haven't learned it, here is the proof.

F^-1(y) = F^-1[F(x)] = x

Differentiate both side with respect to x,

F^-1'(y)F'(x) = 1

which leads to

F^-1'(y) = 1/F'(x)